2011
DOI: 10.1017/s1751731110001485
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid profile of muscle and adipose tissue of lambs fed camelina or linseed as oil or seeds

Abstract: The objective of this study was to evaluate the impact of diets enriched with plant oils or seeds, high in polyunsaturated fatty acids (PUFA), on the fatty acid profile of sheep intramuscular and subcutaneous adipose tissue (SAT). Sixty-six lambs were blocked according to initial body weight and randomly assigned to six concentrate-based rations containing 60 g fat/kg dry matter from different sources: (1) Megalac (MG; ruminally protected saturated fat), (2) camelina oil (CO), (3) linseed oil (LO), (4) NaOH-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 39 publications
4
37
1
Order By: Relevance
“…According to this pattern, the inclusion of linseed in the diet resulted in an increase in t11-18:1, which, in turn, led to an increase in CLA content in the intramuscular fat, especially in the neutral lipids. Similar results have been previously obtained by feeding lambs diets supplemented with linseed oil (Noci et al, 2011). The CLA and t11-18:1 are considered potential bioactive compounds for human health (Mele and Banni, 2010) and the use of linseed in the diet of lambs may be a feasible strategy to enrich meat with these fatty acids.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…According to this pattern, the inclusion of linseed in the diet resulted in an increase in t11-18:1, which, in turn, led to an increase in CLA content in the intramuscular fat, especially in the neutral lipids. Similar results have been previously obtained by feeding lambs diets supplemented with linseed oil (Noci et al, 2011). The CLA and t11-18:1 are considered potential bioactive compounds for human health (Mele and Banni, 2010) and the use of linseed in the diet of lambs may be a feasible strategy to enrich meat with these fatty acids.…”
Section: Resultssupporting
confidence: 83%
“…Two isomers (t4-and t5-18:1) were detected only in neutral lipids. The higher affinity of trans fatty acids for neutral lipids was previously reported, especially when the lambs were fed a diet enriched with 18:3 n-3 (Jerónimo et al, 2011;Noci et al, 2011). According to the pattern of trans-18:1, the biohydrogenation of dietary c9-18:1 contained in the O and OL diets resulted in an accumulation of t5-18:1 t6-8-18:1, t9-18:1, t10-18:1 and t12-18:1, whereas the content of t11-18:1 did not significantly vary when compared with C treatment.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Some authors found an increase of LC-PUFAn-3 in lambs fed linseed diets (Noci et al, 2011;Berthelot et al, 2012), while others did not observe any effect (Bas et al, 2007). Others found that feeding ewes a n-3-enriched diet in lactation increased the proportion of 18:3n-3 and their longer chain derivatives in suckling lamb muscles (Gómez-Cortés et al, 2014;Mele et al, 2014), whereas Berthelot et al (2012) did not report such effects in their earlier experiment.…”
Section: Introductionmentioning
confidence: 94%